Long term unemployment and violent crimes - using post-2000 data to reinvestigate the relationship between unemployment and crime - Daniel Almén; Martin Nordin (Lund University, School of Economics and Management, Department of Economics, 2011)
Abstract This study reinvestigates the relationship between unemployment and crime. By being the first study to use long-term unemployment, it contributes unique findings. Moreover, with a Swedish panel consisting of 288 municipalities and annual data from 1997 to 2009, the relationship is investigated for the first time with aggregate post-2000 data. The results show that long-term unemployment exhibits a strong association with violent crimes in addition to property crimes, highlighting a potential gap in the conventional theories of economics of crime. The point-estimate of long-term unemployment for violent crimes is between 1.5 and 4, and for property crimes it is between 1.3 and 2.3. Thus, long-term unemployment identifies a marginal group for committing crimes, particularly violent crimes, better than total unemployment does. Long-term unemployment plausibly creates a feeling of alienation that fosters violent and other non-rational behaviors.
Keywords: J20; K14; K42; 330; crime; unemployment; long-term unemployment